'Restricted' digital/media repertoires in rural Kenya: a constructive critique. Issue 3 (17th February 2021) - Wildermuth, Norbert
ABSTRACT: The ambition of this article is twofold and consists of an attempt to outline a problematic bias of research attention and interpretation, discernible in the field of studies that address the appropriation and usage of new media and networked communication technologies, as unfolding in Africa. Thus, I voice my concerns in respect to scholarly attempts, quantitative and qualitative in nature, to define those who are left behind at the bottom of the digital/media pyramid, in narrow deterministic terms. Based on qualitative interviews from fieldwork in Uasin Gishu County, Kenya I suggest a methodological–analytical approach to overcome this blind spot of attention and understanding, by show-casing a different strategy of data generation and interpretative reading. The article draws attention on the media practices and routines that are contextually embedded in the lifeworld concerns and pragmatic decisions of individuals located at the excluded end of the continuum of communication ecologies in Kenya. My in-depth presentation and discussion of two protagonists from rural Ziwa ward seeks to challenge commonplace characterisations of the causes and consequences of restricted digital/media repertoires. This includes a rejection of techno-centric, normative claims that define digital inclusion in narrow terms and the excluded as human impediments to democratic transition and development. Instead, I put forward a situated understanding of digital/media repertoires that while realised under constrained conditions, nonetheless allow people to address their lifeworld concerns. Concerns, here understood 'as activities that matter to people' (Helle-Valle, J. (2019). Advocating causal analyses of media and social change by way of social mechanisms. Journal of African Media Studies, 11 (2), 143–161. https://doi.org/10.1386/jams.11.2.143_1), in consequence affecting digital/media practices and vice versa.